1997
DOI: 10.1074/jbc.272.34.21388
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Mitochondrial Hydrogen Peroxide Generation in Ceramide-induced Apoptosis

Abstract: The key events implicated in ceramide-triggered apoptosis remain unknown. In this study we show that 25 M C6-ceramide induced significant H 2 O 2 production within 60 min, which increased up to 180 min in human myeloid leukemia U937 cells. Inactive analogue dihydro-C6-ceramide had no effect. Furthermore, no H 2 O 2 production was observed in C6-ceramide-treated U937 °c ells, which are mitochondrial respiration-deficient. We also present evidence that ceramide-induced activation of the transcription factors NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
318
2
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 471 publications
(337 citation statements)
references
References 55 publications
15
318
2
1
Order By: Relevance
“…We have previously demonstrated that DNR induces DNA fragmentation in the HL60 myeloid cell line (Quillet-Mary et al, 1996). As expected, control HL60/ Neo cells behaved as the parental cell line, with 82.6+9.3% DNA fragmentation after 6 h exposure to 1 mM DNR (Figure 3b, left).…”
Section: Expression Of Bcl-2 and Bax Proteinssupporting
confidence: 78%
See 2 more Smart Citations
“…We have previously demonstrated that DNR induces DNA fragmentation in the HL60 myeloid cell line (Quillet-Mary et al, 1996). As expected, control HL60/ Neo cells behaved as the parental cell line, with 82.6+9.3% DNA fragmentation after 6 h exposure to 1 mM DNR (Figure 3b, left).…”
Section: Expression Of Bcl-2 and Bax Proteinssupporting
confidence: 78%
“…The supernatant (detergent soluble low molecular weight DNA) and pellet (intact chromatin DNA or large chromatin fragments) radioactivity was determined by liquid scintillation counting. Results were expressed as the percentage of fragmented DNA, in which the spontaneous DNA fragmentation of untreated cells had been subtracted, as previously described (Quillet-Mary et al, 1996).…”
Section: Quanti®cation Of Dna Fragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most of the apoptotic stimulus known so far lead ®rst to the Dc m dissipation followed by a hyperproduction of ROS , it has been shown that in other apoptotic systems, ROS production precedes Dc m (France-Lanord et al, 1997; Macho et al, 1998;Quillet-Mary et al, 1997). To study the role of the mitochondria membrane potential and ROS generation in both K562 and K562-Tat cells, we incubated the cells under low serum conditions (0.1% FCS) for di erent times.…”
Section: Loss Of Mitochondrial Membrane Potential (Dc M ) and Reactivmentioning
confidence: 99%
“…Ceramide has been described to activate various cell death mechanisms including mitochondrial recruitment (Kolesnick, 2002). For instance, through interaction with mitochondria, ceramide elicits a burst of reactive oxygen species (ROS) and release of mitochondrial apoptotic proteins, thus engaging the mitochondrial apoptosome (Garcia-Ruiz et al, 1997;Quillet-Mary et al, 1997;Ghafourifar et al, 1999). Other sphingolipids with death-promoting activity include gangliosides, such as ganglioside GD3, which has been shown to mediate apoptosis by a dual mechanism involving interaction with mitochondria and suppression of survival pathways (Scorrano et al, 1999;Garcia-Ruiz et al, 2000;Rippo et al, 2000;Colell et al, 2001;Paris et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%